Faktor-Faktor Yang Mempengaruhi Kualitas Audit Sektor Farmasi (BEI) Tahun 2021-2023 - Septyawan, I Kadek Agus; Ayu , Putu Cita (Hita Akuntansi dan Keuangan, 2025)
This study aims to determine the effect of audit tenure, auditor reputation, and audit committee on audit quality in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The population in this study was all pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period, with a total of 12 companies over the three years of observation. Sampling used a non-probability sampling method with purposive sampling, resulting in a total sample of 36 data. To test the hypothesis, descriptive statistical analysis, classical assumption tests, logistic regression analysis, and coefficient of determination were used using SPSS. The results showed that audit tenure had no effect on audit quality, while auditor reputation and audit committee had a positive effect on audit quality.